TREN FOTO PREWEDDING DI DESA WRINGINPITU KABUPATEN BANYUWANGI - Mahmud, M. Amir (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2021)
Prewedding photos have become an inseparable part of the wedding procession until 40% of the bride and groom in the Wringin Pitu village do it. This paper is intended to complement the shortcomings of existing studies by observing carefully the meaning of pre-wedding photos among Muslim bride and groom in Wringinpitu Village, Tegaldlimo District, Banyuwangi. This research is a descriptive exploratory and phenomenological research type which is taken from qualitative data in the form of field observations, interviews, and documentation as material for analysis, so that the authors can find important findings. The results showed that doing pre-wedding photos has a meaning of self-existence so as not to be outdated and following trends other than for personal documentation. And aims to meet social needs (social needs), the need for self-actualization (self actualization) and the need for appreciation (Esteem Needs). In terms of clothing styles, in general, prospective brides still follow the prevailing religious norms in society.